Microwave-freeze drying of lactic acid bacteria: Influence of process parameters on drying behavior and viability. (August 2018) - Ambros, S.; Mayer, R.; Schumann, B.; Kulozik, U.
Abstract: Microwave-freeze drying was investigated as an alternative to conventional lyophilization to preserve the lactic acid bacteria Lactobacillus paracasei ssp. paracasei F19 ( Lb. paracasei ) and Bifidobacterium animalis ssp. lactis INL1 ( B. lactis ). The process parameters microwave power input (1.5–3 W∗g −1 ) and chamber pressure (0.6, 1, 2 mbar) were varied. Drying kinetics, overall drying time, process stability and energy demand were assessed. Survival rate and cell membrane integrity were evaluated. Survival rate and membrane integrity after microwave-freeze drying were comparable to the standard lyophilization process for both cultures. For Lb. paracasei, survival could almost be maintained at all microwave-freeze drying process conditions. Best results in terms of process stability were achieved at 1 mbar and 1.5 W∗g −1 . For B. lactis, the highest survival of more than 90% was measured at 0.6 mbar and 1.5 W∗g −1 microwave input. These conditions led to a drying time of 5 h, whereas conventional freeze drying lasted 24 h. A potential reduction of drying time compared to freeze drying of bacterial cultures of up to 80% renders microwave-freeze drying an alternative with comparable survival rates but higher efficiency. Highlights: Microwave-freeze drying was investigated as possible drying technique for the preservation of lactic acid bacteria. Survival rates and membrane integrities were comparable to conventional freeze drying. The impact of the chamber pressure on survival and efficiency was higher than the impact of microwave power input. Microwave application in freeze drying can drastically reduce drying time and lead to a more efficient process.